Coordination, cooperation and control within decentralized fiscal systems - Spanh, Paul Bernd (UN SantiagoCL, 1998)
Seeks to demonstrate based on the example of more mature federations in the industrialised world, that there is scope for decentralization without excessive risks for public decision making or the loss of macroeconomic control.